Anesthetic management of peadiatric severe pulmonary stenosis for balloon valvotomy in non-operating room anesthesia: A case of 4 year old male child with severe pulmonary stenosis with peak pressure gradient of 120mmhg underwent balloon pulmonary valvotomy under general anesthesia in non-operating room anesthesia - Arumugam Chandrasekar Malarvizhi; Appukutta Vinothkumar; Sowmiya D.; Raghav J.; Karthikeyan K. (Serbian Journal of Anesthesia and Intensive Therapy)
Balloon pulmonary valvotomy is the treatment of choice in patients with isolated pulmonary stenosis and has shown good long-term results. It is generally considered a safe procedure with fewer complications. We report a case of 4-year-old male child with severe pulmonary stenosis with peak pressure gradient of 120 mmHg underwent balloon pulmonary valvotomy in non-operating room anesthesia.